ASSESSMENT OF CT SCAN INTERPRETATION SKILLS AMONG SURGICAL RESIDENTS OF CIVIL HOSPITAL KARACHI IN TRAUMA CASES - KHAN , B; ZULFIKAR , I; NADEEM , A; SHEIKH , K; TAHIR , S; NADEEM , S (Biological and Clinical Sciences Research Journal, 2024)
Trauma care relies heavily on accurate imaging, particularly CT scans, for effective clinical decision-making. Surgical residents often face challenges in interpreting CT scans, impacting patient outcomes. This study evaluates the CT scan interpretation skills of surgical residents at Civil Hospital Karachi in trauma cases. Objective: To evaluate the CT scan interpretation skills of surgical residents in trauma cases and identify areas requiring improvement to enhance diagnostic accuracy and clinical efficacy. Methods: A cross-sectional study was conducted with 16 surgical residents that were divided into two groups as senior residents (SR- Year 4) and junior residents (JR- Year 3) . Participants analyzed CT scans depicting liver, spleen, kidney injuries, and pneumoperitoneum. Their interpretations were compared with expert radiologists’ diagnoses. Data was analyzed using SPSS version 21 to assess accuracy, confidence, and misclassification trends. Results: Overall diagnostic accuracy was highest for pneumoperitoneum (85%), followed by liver injuries (81.25%), splenic injuries (75%), and renal trauma (68.75%). Senior residents outperformed junior residents, especially in diagnosing complex injuries. Challenges included identifying subtle abnormalities and correlating radiological findings with clinical scenarios. Most residents reported a need for further training in trauma imaging. Conclusion: CT scan interpretation skills among surgical residents at Civil Hospital Karachi vary significantly with experience. Enhanced, structured training in trauma-related radiology is recommended to improve diagnostic accuracy and patient outcomes.